Impact of carbonate mineral heterogeneity on wettability alteration potential of surfactants. (15th June 2023) - AlZaabi, Ahmed; Arif, Muhammad; Ali, Mujahid; Adila, Ahmed; Abbas, Yawar; Kumar, Ravi Shankar; Keshavarz, Alireza; Iglauer, Stefan
Highlights: Performance of anionic and cationic surfactant on wettability of carbonate rock is elaborated. Wettability of carbonate rocks can be improved by optimum surfactant concentration. High temperature implied more hydrophilicity while pressure had a negligible effect. ζ-Potential and contact angle relationship are a function of the type of surfactant. FTIR illustrated presence of CO and Ca-C bonds on surfaces treated with surfactants. Abstract: Surfactants have been widely used for enhanced oil recovery. However, the wettability alteration potential of surfactants as a function of carbonate rock mineralogy remains broadly unclear. Thus, here we investigate the effect of cationic surfactant cetyltrimethylammonium ammonium bromide (CTAB) and anionic surfactant sodium dodecyl benzene sulphonate (SDBS) surfactant on three carbonate rocks and a pure calcite mineral sample under a range of concentrations. Contact angles were measured on all these samples as a function of surfactant concentration. Furthermore, at the critical micelle concentration, advancing and receding contact angles are also measured as a function of pressure (0.1 – 20 MPa) and temperature (303 – 323 K) to reflect the behavior under subsurface conditions. To understand the interactions at the surfactant-mineral interface and its associated impact on wettability alteration, the zeta potential of surfactant-brine-rock emulsions are measured while surface chemical groups are identified by Fourier-transform infrared (FTIR) spectroscopy. The results are further supplemented by Energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction analysis (XRD), and thin section analysis while the surface properties are evaluated by Atomic Force Microscopy (AFM), and Scanning Electron Microscopy (SEM) techniques. The results indicate a notable wettability alteration potential for CTAB turning the calcite surface water-wet while increasing the surfactant concentration did not necessarily yield better wettability alteration. The wettability alteration potential of CTAB is found to correlate with the calcite content of the carbonate sample i.e., a higher calcite content led to a greater reduction in contact angle. Contact angles demonstrate a slight increase with increasing pressure, while they decreased with increasing temperature. Finally, the existence of CO group (carboxylate groups) tends to make the CTAB-treated surface more hydrophilic while the surfaces treated with SDBS did not reveal any notable trend with respect to CO group. The results of this study add to our understanding of the surfactant potential for wettability alteration of carbonate and thus have implications for chemical enhanced oil recovery.